Functional consequences of the inhibition of Malaria S-adenosylmethionine decarboxylase as a key regulator of polyamine and methionine metabolism - Louw, Abraham Izak (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.